Loss of PBRM1 and BAP1 Expression Is Less Common in Non–Clear Cell Renal Cell Carcinoma Than in Clear Cell Renal Cell Carcinoma - Ho, Thai H. (Urol Oncol, 2014)
BACKGROUND: Recurrent mutations in polybromo-1 (PBRM1, ~40%) and BRCA1-associated protein-1 (BAP1, ~10%) occur in clear cell renal cell carcinoma (ccRCC), but their prevalence in non clear cell renal cell carcinoma (non-ccRCC) or renal oncocytoma (RO) is unknown. We evaluated loss of PBRM1 and BAP1 staining in ccRCC, papillary RCC (pRCC), chromophobe RCC (chRCC) and RO tumors using an immunohistochemistry (IHC) assay for which negative staining associates with loss-of-function mutations. METHODS: We identified 458 patients treated surgically for ccRCC, pRCC, chRCC and RO between 2004 and 2012. We performed IHC assays to evaluate PBRM1 and BAP1 protein expression to classify tumors as PBRM1- or BAP1-negative. We compared loss of staining of these 2 proteins in ccRCC and non-ccRCC using Fisher’s exact test. RESULTS: For the total cohort of 458 patients, we successfully stained both PBRM1 and BAP1 in 408 tumor samples. Consistent with the mutation rate, loss of PBRM1 and BAP1 staining occurred in 43% (80/187) and 10% (18/187) of ccRCC respectively. However, loss of PBRM1 staining occurred in only 3% (2/59), 6% (1/17) and 0% (0/34) of pRCC, chRCC and RO tumors, respectively (P<0.0001). BAP1 loss was not observed in any of the pRCC (N=61), chRCC (N=17) or RO (N=34) tumors (P=.00021). CONCLUSION: Our data suggest that biallelic inactivation of PBRM1 or BAP1 is less common in non-ccRCC when compared to ccRCC tumors. These findings suggest that loss of PBRM1 or BAP1 are key events in ccRCC, whereas other pathways may support tumorigenesis in non-ccRCC subtypes.